Preliminary results of vibro-acoustography evaluation of bone surface and bone fracture - Nogueira-Barbosa, Marcello H.; Kamimura, Hermes Arytto Salles; Braz, Guilherme; Agnollitto, Paulo M.; Oliveira Carneiro, Antonio Adilton (Quantitative Imaging in Medicine and Surgery; Vol 7, No 5 (October 31, 2017): Quantitative Imaging in Medicine and Surgery, 2017)
Background: Vibro-acoustography (VA) uses two co-focused ultrasound beams with slightly different frequencies. The beams interact and generate a low-frequency focus to excite an object. Methods: A two-element confocal ultrasound transducer with central frequency at 3.2 MHz was used to generate the low-frequency excitation (30 kHz) and the response of the bone to that excitation was acquired by a dedicated hydrophone. The face of the confocal transducer was positioned parallel to the surface of the bone at a focal length of 7 cm. The hydrophone was fixed to the side of the transducer, out of the path of the ultrasonic beam. Results: The resulting image clearly showed the bone fracture with resolution of 0.25 mm and high contrast with well-defined borders. Conclusions: In this paper, we present preliminary results of VA imaging of bone surface and of bone fracture using an experimental set-up. Our results encourage future studies using VA to evaluate bone fractures.